Synthesis, reactivity and biological activity of 5-alkoxymethyluracil analogues - Brulikova, Lucie (Beilstein-Institut, 2011)
This review article summarizes the results of a long-term investigation of 5-alkoxymethyluracil analogues and is aimed, in particular, at methods of syntheses. Most of the presented compounds were synthesized in order to evaluate their biological activity, therefore, a brief survey of biological activity, especially antiviral, cytotoxic and antibacterial, is also reported.